Sustainable Partnerships in Cassava Production and Industrial Sector: A Heckprobit Analysis of Indonesian Farmers - Ibnu, Muhammad (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
Partnerships are instruments to overcome the inability of individual smallholders to solve the development problems associated with agricultural sectors and commodity chains. While vigorously advocated, a sustainable partnership is rare in the Indonesian cassava production and industrial sector. Knowledge of partnership from the sector is also limited. This study explores the reasons for previous partnerships in the cassava production and industrial sector discontinued and examine what factors determine farmers' willingness to partake in partnerships. The study administered a systematic random sampling to survey for 140 cassava farmers in Central and East Lampung Districts from November 2018 to April 2019. Farmers were interviewed and given a structural questionnaire. The quantitative data were analyzed by heckprobit regression. The results of the study show that the partnership ends because the two parties do not have the same vision for working together. Various variables (barriers to selling to non-industries, low prices, inaccurate weighing scales, high transaction costs, and discounted prices.) indicate the complexity of farmers' considerations for joining the partnership. This research impliesthat it is difficult to create partnerships in the future if farmers and industry have different visions and priorities.